Prospect of Aquaponics for the Sustainable Development of Food Production in Urban - Chunjie Li; Chew Tin Lee; Yueshu Gao; Haslenda Hashim; Xiaojun Zhang; Wei-Min Wu; Zhenjia Zhang (Chemical Engineering Transactions, 2018)
Aquaponics refers to a system that combines aquaculture (raising aquatic animals like fish) with hydroponics (cultivating vegetable plants in water) in a symbiotic environment. This system has great potential as a new industrialised food production approach to meet the needs of rapid urbanisation. An evolutional food production system with high productivity and low resource consumption is desirable. Aquaponics is designed based on excellent ecology recycling system, i.e. the food residues and metabolic products in the effluent of aquaculture are pollutants to the environment; they are also the source of nutrients that can be converted and mineralised via microbial treatment and eventually up taken by plants in the hydroponics section. The effluent of hydroponics section is then recycled as clean water for the aquaculture section. Home-based aquaponics (HA), factory- based aquaponics (FA) and building-based aquaponics (BA) are the typical forms of aquaponics for different urban development. The sustainability of aquaponics practices is evaluated using the “triple-bottomline” approach, which requires assessment of impacts on environmental, economic and societal systems. There is a lack of systematic research and modelling work reported on aquaponics, especially in terms of ecological manipulation. Understanding the conversion of the pollutants in the combined system is essential to achieve the optimal manipulation of ecology for optimal system operation. Future work will focus on the production of pollutants in aquaculture, the conversion and degradation of the pollutants in the microbial treatment section, and uptake of organic nutrients and inorganic salts in the hydroponics section. Development of a model, capable of describing the release of pollutants, conversion and uptake of nutrients and the production of metabolic products, is desirable. The model could be developed based on the mass balance of nutrition, productivity of fish and plants and the environmental factors. The aquaponics system could be simulated and analysed using this model so as to provide an optimal system for the design and implementation of different type of aquaponics.